Heteroleptic diphosphenes and arsaphosphenes bearing neutral and anionic N-heterocyclic carbenes. Issue 72 (20th August 2019) - Ho, Luong Phong; Zaretzke, Marc-Kevin; Bannenberg, Thomas; Tamm, Matthias
Abstract : A modular approach afforded heteroleptic arsaphosphene species supported by neutral and anionic N-heterocyclic carbenes. Abstract : The reaction of the phosphorus and arsenic dihalides (WCA-IDipp)ECl2 (E = P, As) that bear an anionic N-heterocyclic carbene ligand with a weakly coordinating borate moiety (WCA = B(C6 F5 )3, IDipp = 1, 3-bis(2, 6-diisopropylphenyl)imidazolin-2-ylidene) with (IDipp)PSiMe3 afforded the monochlorides (WCA-IDipp)E(Cl)P(IDipp), which can be transformed into the cationic dipnictenes [(WCA-IDipp)EP(IDipp)][GaCl4 ] or neutral radicals [(WCA-IDipp)EP(IDipp)] by treatment with GaCl3 or reduction with 1, 4-bis(trimethylsilyl)-1, 4-dihydropyrazine.